Metamorphosis of the osmoregulatory processes of the Baltic salmon in the migration period - Klyavsons, Yu.A. (Baltijskij Nauchno-issledovatelskij Institut Rybnogo Khozyajstva, 1970)
The results of the investigations on blood of salmon (Salmo salar L.) during the migration are presented. It was indicated that with the beginning of smoltification a jump in the osmotic concentration in blood takes place. It is probably an adaptive phenomenon and helps the smolts overcome the salinity barrier during their migration to the sea. Also the increase in the serum albumin, the haemoglobin content in blood and some degradation in the muscle tissue in the smoltification period was studied. The decreased diuresis of smolts indicates a drop in the water content in their body. In addition, an active absorption of inorganic ions by their gills takes place. This specific character of the water- salt exchange favours the increase in the concentration of the osmotically active compounds in the blood and maintains the constancy of the internal medium of the organism. Published Not Known